Coordenador pedagógico da Educação Infantil e as necessidades formativas na escola: enfrentamentos e possibilidades - Matos, Priscila Conceição Gambale Vieira (2020)
The present research aimed at investigating which are the training needs of Kindergarten pedagogical coordinators in Ferraz de Vasconcelos - SP. For that, we have proposed the following objectives: (a) discover what concept of childhood coordinators who work in the city have; (b) identify what they consider to be challenges when carrying out continuous training with their groups of teachers at school; (c) highlight what they consider to be significative training and detect evidences of their training needs. As the first step in basic education, Kindergarten is the beginning and the foundation for humans’ educational process. With that in mind, in this study, we discuss that, with the evolution of this teaching category, the necessity of training for teachers who teach this segment has grown, as well as the definition of trainers’ profile and function. This research has been carried out with 21 Kindergarten pedagogical coordinators from the city, some of them training teachers who work with babies in Nursery School (de zero to three y-o) and some with little children (four to five y-o). Theoretical foundation is based on authors who study the roles of pedagogical coordinators, including Almeida e Placco. Research suggests that, when continuous training at school provides moments for reflection about the teachers’ practices, respecting their work contexts and the moments of exchange among peers, productive decision-making moments are enabled for teachers. Data have been produced through questionnaire and discussion group. Corpus has been analyzed according to methodological procedures of Bardin’s Content Analysis. Results found reveal that the coordinators’ concept of childhood is in accord to the educational principles that guide the Brazilian Common Core Curriculum (Base Nacional Comum Curricular – BNCC); they also reveal which the greatest challenges faced by these professionals are when providing training, among them are the excessive management demands, diversion of function and routine organization. Articulation between theory and practice has been pointed out as essential component for significative training; as to their training needs, it has been possible to conclude that they long for more training studies meetings, and that, in these meetings, methodological aspects of trainers practices were emphasized. We expect the reflections raised by this research could contribute for expanding pedagogical coordinators’ training field with the group of teachers at Kindergarten schools, gathering elements to reorganize time, spaces and situations that could ensure all children’s learning rights